MODELS OF MULTICULTURAL PREPARATION BACHELORS (EXPERTS) IN THE CONDITIONS OF HOLISTICHNY INFORMATION AND EDUCATION SPACEINFORMATION AND EDUCATION SPACE - Vladimir N. Aniskin; Vladimir I. Bogoslovsky; Tatyana A. Zhukova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The relationships of cause and effect of multicultural crisis in system of higher education caused by imperfection of the main educational programs of higher education institutions which don't promote training of students in the field of multicultural relationship are consid-ered. For increase of efficiency of multicultural training of bachelors (experts) the innovative model which basis are the holistichny information and education environment and holistichny information and education space is offered. On the basis of development of known idea of the holistichny environment of educational institution author's definitions and characteristics of the holistichny information and education environment and holistichny information and educa-tion space are given. Degree of interrelation of the holistichny information and education en-vironment and holistichny information and education space in which there is a training of bachelors integrators (specialists integrators) to new type of multicultural thinking and the self-organization capable quickly is analyzed and correctly to adapt for the changing condi-tions, to be able to predict the closest and perspective consequences of the changes happening in the sphere of their professional activity. The assumption of that locates, bachelors integra-tors (specialists integrators) prepared in the conditions of holistichny information and educa-tion space possess the organizing qualities of the teacher, psychologist, culturologist, political scientist, a desmoekolog allowing to solve problems of the multicultural contents and to pro-mote overcoming of consequences of multicultural crisis. The general structural model of sys-tem and integrative holistichny information and education space, the most effective for multi-cultural training of bachelors (experts) is given. Models of the diverse dismembered, monoto-nous and uniform and diverse and uniform multicultural training of the bachelor (expert) in the conditions of holistichny information and education space are projected.